Em xem lại đề bài ý thứ 4 nhé
\(\begin{array}{l}
8a + 12b = 4\left( {2a + 3b} \right)\\
3x\left( {x - 3} \right) + 2\left( {x - 3} \right) = \left( {x - 3} \right)\left( {3x + 2} \right)\\
{m^2} - mx - 5m + 5x = m\left( {m - x} \right) - 5\left( {m - x} \right) = \left( {m - x} \right)\left( {m - 5} \right)\\
9{x^2} - 12xy + 4{y^2} = {\left( {3x} \right)^2} - 2.3x.2y + {\left( {2y} \right)^2} = {\left( {3x - 2y} \right)^2}\\
{x^2} + 2xy + x + 2y = x\left( {x + 2y} \right) + \left( {x + 2y} \right) = \left( {x + 2y} \right)\left( {x + 1} \right)
\end{array}\)